The first case of novel variants of the mutation causing primary amenorrhea in 2 siblings in Korea - Sukdong Yoo; Ju Young Yoon; Changwon Keum; Chong Kun Cheon (Korean Society of Pediatric Endocrinology, 2022)
Follicle-stimulating hormone receptor (FSHR) mutation is a rare cause of amenorrhea. We report the first case of FSHR mutations in Korea. Two female siblings, aged 16 (patient 1) and 19 (patient 2) years, were referred to the pediatric endocrinology clinic because of primary amenorrhea despite normal breast budding. Gonadotropin-releasing hormone stimulation test showed markedly elevated luteinizing hormone and follicle-stimulating hormone with a relatively low level of estrogen, suggesting hypergonadotropic hypogonadism. Pelvic magnetic resonance imaging revealed a bicornuate uterus in patient 1 and uterine hypoplasia with thinning of the endometrium in patient 2. The progesterone challenge test revealed no withdrawal of bleeding. After two months of administration of combined oral contraceptives, menarche was initiated at regular intervals. To determine the genetic cause of amenorrhea in these patients, whole exome sequencing (WES) was performed, which revealed a compound heterozygous FSHR mutation, c.1364T>G (p.Val455Gly) on exon 10, and c.374T>G (p.Leu125Arg) on exon 4; both of which were novel mutations and were confirmed by Sanger sequencing. The patients maintained regular menstruation and improved bone mineral density while taking combined oral contraceptives, calcium, and vitamin D. Therefore, FSHR mutations can be the cause of amenorrhea in Koreans, and WES facilitates diagnosing the rare cause of amenorrhea.